PTU-203 Hemorpex – effective and safe day case surgical treatment of haemorrhoids in a uk colorectal unit. (22nd June 2015) - Tozer, P; Hollingshead, J; Hubbard, T; Kanapathippillai, R; Smith, J
Abstract : Introduction: The gold standard surgical option for symptomatic haemorrhoids remains haemorrhoidectomy due to its low recurrence rate but alternative options with less postoperative pain (and a slightly higher recurrence rate of around 10–20%) include stapled anopexy and haemorrhoidal artery ligation procedures. Hemorpex is a newer and cheaper technique in which arterial ligation is performed without the need for an expensive doppler probe. Previous studies have reported success rates of 70–90% with little postoperative pain. We present our first 3 years' experience with this technique. Method: Retrospective data were collected from hospital records on consecutive patients undergoing the Hemorpex procedure in a single centre over a 3 year period from June 2009 to June 2012. Patients under general or regional anaesthesia in the prone position had 6 spiral sutures placed in the 1, 3, 5, 7, 9 and 11 o'clock positions using the Hemorpex operating proctoscope. Skin tag excision was performed concurrently where appropriate. Demographic and outcome data were collected including admission, readmission, recurrence rates and postoperative complications. Results: Some 248 patients underwent Hemorpex, as a day case in 94% of cases. The mean operating time was 27 min (SD 9.8 min). General anaesthesia (68%), spinal (30%) or caudal epidural (1%) were used. Early postoperative complications included acute urinary retention (4%), post-operative pain (3%) and minor post-operative bleeding (3%) none of whom required overnight admission. Nine percent required readmission, mostly for pain or bleeding. Fifteen percent presented with recurrence. Twelve percent required reintervention of whom half underwent redo Hemorpex or haemorrhoidectomy and a third required either office based treatment or skin tag excision. Conclusion: Hemorpex is a successful day case technique for the surgical management of haemorrhoids with low morbidity and recurrence rate equivalent to similar procedures but without equivalent cost. Disclosure of interest: None Declared.